Michael Faraday La storia romantica di un genio - Meurig, Thomas John (Studi e saggi, 2006)
Michael Faraday, a self-taught errand boy of humble origins with no particular knowledge of mathematics, became one of the greatest Englishmen of all times. With simple determination and extraordinary insight he was able to make the scientific discoveries on which most of the technology of the twentieth century is based. His life and works have profoundly influenced contemporary thought, inspiring and complementing the work of other great minds, such as Clerk Maxwell and Albert Einstein. John Meurig Thomas is continuing a tradition of popularisation of science that has a shining example in Michael Faraday; Sir Thomas has the merit of illustrating the history and scientific work of this philosopher of nature with a simple and at the same time accurate style, which is accessible to all. Faraday's fascinating and detailed story is enriched with a series of drawings, photographs and letters, mostly unpublished documents.